Analysis of the Efficiency of a Microcontroller-Based Automatic Feeder Prototype in Aquaculture - Ashari, Faisal; Stighfarrinata, Rizky; Zahra, Nayla Farikha (Lembaga Penelitian dan Pengabdian kepada Masyarakat ITATS, 2025)
This research aims to analyze the efficiency of a microcontroller-based automatic fish feeder prototype to support the optimization of aquaculture. The device utilizes an Arduino microcontroller, an LCD for the interface, and a mechanical motor for automatic feed dispensation twice daily, with volumes adjusted according to the fish's age. The experimental method was conducted in a fish farming pond, comparing automatic and manual feeding over 90 days for 100 fish. Results showed that the automatic system reduced average daily feed usage from 200 grams (manual) to 180 grams, and feed efficiency increased from 75% (manual) to 85% (automatic). Average fish weight gain with the automatic system reached 85 grams, 15 grams higher than the manual method (70 grams). The Feed Conversion Ratio (FCR) for the automatic system was 1.91, which is better than the manual FCR of 2.57. Ultimately, the automatic feeding system proved to be more efficient in feed usage and supported better fish growth. Keywords: Automatic Feeder, Efficiency, Aquaculture.